Analisis Peran Dual Banking System dalam Perspektif Ilmu Ekonomi Syariah - Dika Nugraha; Tesya Erfani; Tsabita Fithriya; Ramiza Maghfira (Jurnal Ilmiah Ekonomi Islam, 2023)
Banking in Indonesia each adheres to a dual banking system in which there are two operating systems, namely sharia and conventional. With the majority of Indonesia's population being Muslim, the fact is that there are still many who prefer conventional banking. This choice occurs because people think that Islamic and conventional banking are the same. The method we use is a literature study approach and uses secondary data. Data shows that Islamic banking has a good role in supporting the economy in terms of economic stability that is not easily affected or dependent on external factors such as interest rates. The role of the dual banking system in an Islamic economic perspective has the potential to be optimized by adopting the advantages of each banking system.